2019
DOI: 10.1111/jcpp.13076
|View full text |Cite
|
Sign up to set email alerts
|

Retraction: Randomized controlled trial of vitamin D supplementation in children with autism spectrum disorder

Abstract: 95 cases itself. A number of significant discrepancies emerged between the re-analysis and the findings reported in the paper both in terms of means and standard deviations of key outcome variables across the trial. These involved very substantial differences that we judged to be extremely unlikely to have arisen due to variations in composition of the original and re-analysed samples. We also discovered previously unidentified/reported problems with missing data and recording irregularities regarding changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…In an year-long study, Infante et al [66] suggested that a combination of omega-3 and vitamin D supplementation could effectively improve the core symptoms in children with autism. Saad et al [49] found a significant symptom improvement after appropriate vitamin D supplementation in children with autism. However, Kerley et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an year-long study, Infante et al [66] suggested that a combination of omega-3 and vitamin D supplementation could effectively improve the core symptoms in children with autism. Saad et al [49] found a significant symptom improvement after appropriate vitamin D supplementation in children with autism. However, Kerley et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the included children with autism had serum vitamin D levels < 30 ng/ml, which was inconsistent with the inclusion criteria of the present study; therefore, it was excluded. After full text screening, four RCT articles met the inclusion criteria; however, among them, the article of Saad et al [49] was retracted because the validity of the research results was not demonstrated [50,51]. Ultimately, three RCTs were included in the analysis.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The autism severity and social maturity of the children were assessed by the Childhood Autism Rating Scale (CARS), Aberrant Behavior Checklist (ABC), Social Responsiveness Scale (SRS), and the Autism Treatment Evaluation Checklist (ATEC). The ASD children generally tolerated well the supplementation with vitamin D. The autism symptoms of the children improved signifi cantly, following 4 months of vitamin D3 therapy [4]. Vitamin D has an important role in the regulation of both innate and adaptive immune responses.…”
Section: Editorialmentioning
confidence: 90%
“…Vitamin D has an important role in brain homeostasis, neurodevelopment, ageing, and signifi cantly, in gene regulation. Also, it has been shown to bind to more than 2700 genes and to regulate the expression of more than 200 of them [2,[4][5][6]. Many studies suggested that vitamin D has an important role as a neuroactive steroid, which can affect neuronal differentiation, axonal connectivity and brain structure and function.…”
Section: Editorialmentioning
confidence: 99%
“…Moreover, two of those that have reported positive results (83,84) have been largely debated for the methods used to collect data and to evaluate results (85,86). Furthermore, the most recent research has been retracted because a re-analysis of the data collected with the study discovered previously unidentified problems with missing data and recording irregularities that led the Editors to have no longer confidence in the findings reported (87). Consequently, these studies do not offer any reliable information and highlight how much readers must be vigilant when they try to draw firm conclusions from published studies.…”
Section: Therapymentioning
confidence: 99%